1999
DOI: 10.1055/s-2007-1013099
|View full text |Cite
|
Sign up to set email alerts
|

The Urgent Pulmonary Embolectomy: Mechanical Resuscitation in the Operating Theatre Determines the Outcome

Abstract: Pulmonary embolectomy (on the beating heart with ECC under total bypass) under stable hemodynamics, without CPR however, still constitutes an important form of treatment of acute massive PE with excellent long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 11 publications
4
21
0
Order By: Relevance
“…[113][114][115][116][117][118][119][120][121] Alternatively, surgical embolectomy has also been used successfully in some patients after PE-induced cardiac arrest. 117,[122][123][124][125] Mechanical thrombectomy was employed in a small case series and only one of seven patients died and pulmonary perfusion was restored in the majority (85.7%). 115 In post-cardiac arrest patients with arrest due to presumed or known pulmonary embolism, fibrinolytics may be considered (Class IIb, LOE C).…”
Section: Treatment Of Pulmonary Embolism After Cprmentioning
confidence: 99%
“…[113][114][115][116][117][118][119][120][121] Alternatively, surgical embolectomy has also been used successfully in some patients after PE-induced cardiac arrest. 117,[122][123][124][125] Mechanical thrombectomy was employed in a small case series and only one of seven patients died and pulmonary perfusion was restored in the majority (85.7%). 115 In post-cardiac arrest patients with arrest due to presumed or known pulmonary embolism, fibrinolytics may be considered (Class IIb, LOE C).…”
Section: Treatment Of Pulmonary Embolism After Cprmentioning
confidence: 99%
“…247 Five retrospective reviews demonstrated that pulmonary embolectomy following cardiac arrest had a high mortality rate (LOE 4). [753][754][755][756][757] One case series reported outcomes of 7 patients who had a cardiac arrest caused by pulmonary embolism and who were treated with percutaneous mechanical thrombectomy (LOE 4) 720 ; 3 patients also received recombinant tissue plasminogen activator. Only 1 of the 7 patients died and pulmonary perfusion was restored in the majority (85.7%).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Circulatory failure occurs through a profound decrease in left ventricular preload. 6 Therapies such as thrombolysis [7][8][9] or surgical embolectomy [10][11][12][13][14][15] are presumed to reduce mortality, and both methods have been performed even in ongoing CPR situations, either alone or in combination.…”
Section: Arch Intern Med 2000;160:1529-1535mentioning
confidence: 99%
“…26 Surgical embolectomy for the treatment of cardiac arrest caused by PE is useful as an alternative method, especially after failure of thrombolysis or when this is contraindicated, eg, in case of previous major trauma and/or recent surgery. Some authors [10][11][12][13][14][15] report that surgical embolectomy in patients having an episode of cardiac arrest after PE is associated with mortality rates of between 50% and 74% ( Table 6). In our study, in only 1 patient was embolectomy performed because of hemodynamic instability.…”
Section: Commentmentioning
confidence: 99%